Adding double carbapenem therapy to the armamentarium against carbapenem-resistant Enterobacteriaceae bloodstream infections. Issue 3 (4th March 2019) - White, Bryan P.; Patel, Smit; Tsui, Janice; Chastain, Daniel B.
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) constitute a threat, since they cause infections with high mortality rates. Historically, polymyxin-based therapies have been the regimens of choice for CRE bloodstream infection (BSI). Recent studies have shown improved outcomes with β-lactam-based therapies, including double carbapenem regimens for CRE BSIs compared to polymyxin-based regimens. The purpose of this report was to review the data supporting double carbapenem therapy for CRE BSI and provide recommendations regarding their use. Methods: A systematic literature search through 31 January 2018 was performed. Results: Multiple in vitro studies have described synergistic activity with ertapenem-based double carbapenem regimens for KPC-producing Enterobacteriaceae. Additionally, efficacy has been observed with double carbapenem regimens in multiple case reports and case series. A prospective multi-centre observational study of double carbapenem therapies in patients with CRE BSIs showed lower mortality compared to standard therapy. Conclusions: Clinicians should consider double carbapenem therapy as an option for treating CRE infections.